High-entropy alloy particle reinforced 2xxx series aluminum-based composite material and preparation method and application thereof
High-entropy alloy particle-reinforced 2xxx series aluminum-based composites are prepared by mechanical stirring and ultrasonic-assisted methods, which solves the problem of tensile performance degradation of traditional 2xxx series aluminum alloys at high temperatures, achieves improved strength and plasticity of the material at high temperatures, and improves interface stability and organizational uniformity.
Patent Information
- Application Number
- CN202510971175.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-09-05
AI Technical Summary
The tensile properties of traditional 2xxx series aluminum alloys decline sharply and their plasticity decreases significantly under high-temperature environments. Existing alloy design and heat treatment technologies make it difficult to balance high-temperature strength and interface stability, limiting their application in higher service temperature areas.
High-entropy alloy particles are added to the aluminum alloy melt by combining mechanical stirring with ultrasonic assistance. The cavitation effect and acoustic streaming effect of ultrasound promote particle dispersion and interface wetting to form a uniform distribution, thereby preparing high-entropy alloy particle-reinforced 2xxx series aluminum-based composites.
Significantly improve the tensile strength and plasticity retention of materials in high temperature environments, improve organizational uniformity, reduce casting defects, and enhance interface bonding strength and thermal stability.
Smart Images

Figure CN120591600A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal material casting, and in particular to a high-entropy alloy particle reinforced 2xxx series aluminum-based composite material, a preparation method thereof, and an application thereof. Background Art
[0002] In the manufacturing of high-end equipment such as aerospace, automobile engines, and rail transportation, the triple requirements of "lightweight, high strength, and high-temperature stability" are put forward for structural materials. As a typical high-strength heat-treatable aluminum alloy, 2xxx series (Al-Cu based) aluminum alloys are widely used in aviation structural parts, especially in connectors, shells, reinforcements and other components that are subjected to cyclic thermal loads and strong tensile conditions. However, the tensile properties of traditional 2xxx series aluminum alloys decline sharply in high temperature environments (≥200°C), and the plasticity decreases significantly, which becomes a bottleneck restricting its expansion in the field of higher service temperatures. Existing alloy design and heat treatment technologies are difficult to take into account both high-temperature strength and interface stability at the same time. Therefore, there is an urgent need to develop a new preparation technology based on composite reinforcement to improve its tensile properties at high temperatures and promote its application in hot ends, dynamic loads and extreme service environments. Summary of the Invention
[0003] In view of this, the present application provides a high-entropy alloy particle reinforced 2xxx series aluminum-based composite material and its preparation method and application. The method combines mechanical stirring and ultrasonic assistance, with the aim of fully dispersing and wetting the particles in the melt, significantly improving the problems of coarse traditional casting structure, agglomeration of reinforcement phases, and interface instability, thereby effectively improving the tensile strength, plasticity retention ability and organizational uniformity of the material in a high-temperature environment, and can effectively overcome the defects of the above-mentioned existing technologies.
[0004] In a first aspect, the present application provides a method for preparing a high-entropy alloy particle-reinforced 2xxx series aluminum-based composite material, comprising the following steps:
[0005] The 2xxx series aluminum alloy is heated and melted, and stirred after cooling. High entropy alloy particles are added and an inert gas is introduced. Ultrasonic treatment is performed under continuous stirring, and a high entropy alloy particle-reinforced 2xxx series aluminum-based composite material is obtained after casting.
[0006] The introduction of Ultrasonic-Assisted StirCasting (UAS) on the basis of traditional mechanical stirring casting can further enhance the microstructure control capability and performance uniformity of 2xxx series dissimilar aluminum alloy composites. Specifically, mechanical stirring achieves the initial dispersion of the reinforcing phase through macroscopic flow, while ultrasound utilizes the cavitation effect and acoustic streaming effect at the microscale to effectively break up particle agglomeration, promote interfacial wetting and uniform deposition of the reinforcing phase. It is particularly suitable for dispersing reinforcing phases such as nano- or submicron-sized high-entropy alloy particles and ceramic particles. In actual operation, the coupling of these two processes not only improves the interfacial bonding strength and thermal stability of aluminum-based composites, but also reduces the probability of casting defects such as pores and inclusions.
[0007] Preferably, the composition of the 2xxx series aluminum alloy material includes, by weight percentage: Cu 3-6.8%, Mg 0.2-1.5%, Mn 0.2-1.5%, Si ≤0.5%, Fe ≤0.5%, Zn ≤0.25%, Cr ≤0.10%, Ti ≤0.15%, other impurities ≤0.15, and Al balance.
[0008] Preferably, the high entropy alloy particles are FeCoCrNiAl x Ti y , where 0 <x≤1,0<y≤1。
[0009] Preferably, the heating melting temperature is 750° C. and the holding time is 2 hours.
[0010] Preferably, the temperature is lowered to 580-720°C.
[0011] Preferably, the inert gas is argon.
[0012] Preferably, the stirring temperature is 680-720° C., the stirring speed is 400-600 rpm, and the stirring time is 5-15 min.
[0013] Preferably, the ultrasonic frequency is 15-25 kHz, the ultrasonic power is 800-1500 W, and the ultrasonic time is 5 min.
[0014] The second aspect of the present application also provides a high-entropy alloy particle-reinforced 2xxx series aluminum-based composite material, which is a high-entropy alloy particle-reinforced 2xxx series aluminum-based composite material prepared by the above method.
[0015] The third aspect of the present application also provides the application of the above-mentioned high-entropy alloy particle reinforced 2xxx series aluminum-based composite materials in the aerospace field.
[0016] Compared with the prior art, this application has the following beneficial effects:
[0017] This application adopts FeCoCrNiAl x Ti y A stir-casting process for high-entropy alloy (HEA) particles reinforced 2xxx aluminum alloys was developed. By rationally controlling each preparation step, the mechanical properties of the composites under high-temperature conditions were effectively improved. First, the aluminum matrix was heated to 750°C and melted for 2 hours. Next, HEA particles were slowly added to the 2xxx aluminum alloy melt at approximately 700°C, followed by mechanical stirring to enhance initial particle dispersion and mixing uniformity. To further improve the distribution quality, ultrasonic-assisted treatment was introduced to effectively break up particle agglomerates, clean the interface, and promote the formation of a dispersed distribution of particles within the matrix through cavitation and acoustic streaming. The melt was then poured into a metal mold preheated to 200°C and cooled to form a composite casting with a dense and uniform structure. Finally, the relevant heat treatments were performed. Finally, the yield strength, tensile strength, and elongation of the material were systematically evaluated through tensile testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the present application or the prior art, the following briefly introduces the drawings required for use in the description of the present application or the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0019] Figure 1 This is the morphology of high entropy alloy particle reinforced 2xxx series aluminum matrix composites;
[0020] Figure 2 The present invention is a flow chart of the preparation method of high entropy alloy particle reinforced 2xxx series aluminum-based composite materials. DETAILED DESCRIPTION
[0021] To make the objectives, technical solutions, and advantages of this application more clear, the technical solutions of this application will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the embodiments described are only part of the embodiments of this application, not all of them. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of this application.
[0022] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0023] In the following examples and comparative examples, unless otherwise specified, all raw materials can be purchased commercially or prepared by conventional methods.
[0024] Example 1:
[0025] like Figure 2 As shown in the figure, this embodiment uses 2024 aluminum alloy (Cu 4.20%, Mn 0.76%, Mg 1.40%, Fe 0.16%, Si 0.08%, Zn 0.05%, Ti 0.01%, Ni <0.01%, Al balance) as the matrix material, and adds 10wt% of FeCoCrNiAl preheated at 200℃. 0.5 Ti 0.5 High-entropy alloy powder (Fe 20.82wt%, Co 22.25%, Cr19.71%, Ni Bal., Al 5.03wt%, Ti 9.13%, C 0.016wt%, S 0.0017wt%, O 0.028wt%, N0.0011wt%; particle size distribution: D10 8.973μm, D50 15.367μm, D90 25.975μm), with mechanical stirring assisted by ultrasonic waves.
[0026] The aluminum alloy was heated to 750°C and held for 2 hours. After cooling to 700°C, mechanical stirring was started at 500 rpm for 8 minutes. Simultaneously, high-entropy alloy particles were slowly added within the first 3 minutes, with a small amount of argon gas introduced for protection. Ultrasound was applied immediately after the high-entropy alloy addition was completed. The ultrasonic vibrator was inserted approximately 25 mm below the liquid surface and ultrasonic vibration was activated at a frequency of 20 kHz and a power of 1000 W for 5 minutes. After both mechanical stirring and ultrasonication were completed, the melt was poured into a 200°C preheated mold and allowed to cool naturally.
[0027] The demolded casting was used to prepare tensile specimens using wire cutting, and tensile tests were conducted at room temperature (25°C) and high temperature (200°C): the yield strength at room temperature was 338.7MPa, the tensile strength was 472.6MPa, and the elongation after fracture was 6.87%; the yield strength at high temperature was 268.5MPa, the tensile strength was 351.8MPa, and the elongation after fracture was 7.43%. The high-frequency vibration generated by ultrasound in the melt promotes grain refinement and improves the wettability of the matrix and high-entropy alloy particles through cavitation and acoustic streaming effects, resulting in a more uniform distribution of high-entropy particles compared to comparative example 1. Figure 1 As shown, the uniform distribution enables high entropy particles to hinder the expansion of cracks and dislocations caused by tensile stress, thereby improving the yield strength and tensile strength to a certain extent, which is also intuitively reflected in the elongation.
[0028] Comparative Example 1:
[0029] In this comparative example, 2024 aluminum alloy (Cu 4.20%, Mn 0.76%, Mg 1.40%, Fe 0.16%, Si 0.08%, Zn 0.05%, Ti 0.01%, Ni <0.01%, Al balance) was used as the matrix material, and 10 wt% of FeCoCrNiAl preheated at 200 °C was added. 0.5 Ti 0.5 High-entropy alloy powder (Fe 20.82wt%, Co 22.25%, Cr 19.71%, Ni 81.3%, Al 5.03wt%, Ti 9.13%, C 0.016wt%, S 0.0017wt%, O 0.028wt%, N 0.0011wt%; particle size distribution: D10 8.973μm, D50 15.367μm, D90 25.975μm). Neither stirring nor ultrasonic assistance was used.
[0030] The aluminum alloy was heated to 750°C and kept warm for 2 hours. After the temperature was lowered to 700°C, high-entropy alloy particles were slowly added within 3 minutes, and a small amount of argon gas was introduced for protection. After 5 minutes, the melt was poured into a 200°C preheated mold and cooled naturally.
[0031] The demolded casting was used to prepare tensile specimens using the wire cutting method, and tensile tests were carried out at room temperature (25°C) and high temperature (200°C): the yield strength at room temperature was 308.2 MPa, the tensile strength was 426.4 MPa, and the elongation at break was 5.90%; the yield strength at high temperature was 226.7 MPa, the tensile strength was 268.1 MPa, and the elongation at break was 5.28%.
[0032] Comparative Example 2:
[0033] In this comparative example, 2024 aluminum alloy (Cu 4.20%, Mn 0.76%, Mg 1.40%, Fe 0.16%, Si 0.08%, Zn 0.05%, Ti 0.01%, Ni <0.01%, Al balance) was used as the matrix material, and 10 wt% of FeCoCrNiAl preheated at 200 °C was added. 0.5 Ti 0.5 High-entropy alloy powder (Fe 20.82wt%, Co 22.25%, Cr 19.71%, Ni 211%, Al 5.03wt%, Ti 9.13%, C 0.016wt%, S 0.0017wt%, O 0.028wt%, N 0.0011wt%; particle size distribution: D10 8.973μm, D50 15.367μm, D90 25.975μm). Mechanical stirring was performed without ultrasonic assistance.
[0034] The aluminum alloy was heated to 750°C and kept warm for 2 h, then cooled to 700°C and mechanical stirring was started at 500 rpm for 8 min. At the same time, high-entropy alloy particles were slowly added within 3 min, and a small amount of argon gas was introduced for protection. After stirring was completed, the melt was poured into a 200°C preheated mold and cooled naturally.
[0035] The demolded casting was used to prepare tensile specimens using the wire cutting method, and tensile tests were carried out at room temperature (25°C) and high temperature (200°C): the yield strength at room temperature was 319.5 MPa, the tensile strength was 449.3 MPa, and the elongation at break was 6.45%; the yield strength at high temperature was 243.1 MPa, the tensile strength was 304.2 MPa, and the elongation at break was 6.08%.
[0036] Comparative Example 3:
[0037] In this comparative example, 2024 aluminum alloy (Cu 4.20%, Mn 0.76%, Mg 1.40%, Fe 0.16%, Si 0.08%, Zn 0.05%, Ti 0.01%, Ni <0.01%, Al balance) was used as the matrix material, and 10 wt% of FeCoCrNiAl preheated at 200 °C was added. 0.5 Ti 0.5 High-entropy alloy powder (Fe 20.82wt%, Co 22.25%, Cr 19.71%, Ni 81.3%, Al 5.03wt%, Ti 9.13%, C 0.016wt%, S 0.0017wt%, O 0.028wt%, N 0.0011wt%; particle size distribution: D10 8.973μm, D50 15.367μm, D90 25.975μm). Ultrasonication was used instead of stirring.
[0038] The aluminum alloy was heated to 750°C and held for 2 hours. After cooling to 700°C, high-entropy alloy particles were slowly added over the first 3 minutes, with a small amount of argon gas flowing through. Immediately after the addition of the high-entropy alloy particles, ultrasound was applied. The ultrasonic vibrator was inserted approximately 25 mm below the liquid surface. Ultrasonic assistance was activated at a frequency of 20 kHz and a power of 1000 W for 5 minutes. After the ultrasonic vibration ended, the melt was poured into a 200°C preheated mold and allowed to cool naturally.
[0039] The demolded casting was used to prepare tensile specimens using the wire cutting method, and tensile tests were carried out at room temperature (25°C) and high temperature (200°C): the yield strength at room temperature was 328.4 MPa, the tensile strength was 458.7 MPa, and the elongation at break was 5.11%; the yield strength at high temperature was 256.9 MPa, the tensile strength was 329.1 MPa, and the elongation at break was 5.69%.
[0040] Comparative analysis conclusions:
[0041] 1) Comparing Comparative Examples 1 and 2, it is shown that the macroscopic flow induced by stirring enhances the initial uniform dispersion of particles in the melt, reduces agglomeration, and reduces segregation. Comparing Comparative Example 3 with Example 1, the ultrasonically-assisted Example 1 complements the two in terms of particle spatial dispersion and grain refinement. While the interface quality of Comparative Example 3, which lacks stirring, is good, localized agglomerations or porosity still exist in the microstructure, affecting overall ductility.
[0042] 2) Comparison between Comparative Example 1 and Comparative Example 3 shows that ultrasonic cavitation can effectively break up agglomerates, clean oxide films, and improve particle wettability and interfacial bonding ability. However, due to the lack of macroscopic convection support, its spatial distribution uniformity is still not as good as that of the stirring group. Comparative Example 2 and Example 1 show that single stirring can only preliminarily disperse the particles, while the addition of ultrasound can break up microagglomerates, inhibit sedimentation and inclusion defects, and thus bring about more comprehensive performance enhancement.
[0043] Test example:
[0044] After solidification, the castings were demolded and cut into tensile specimen blanks. The specimen dimensions were precision-machined according to GB / T 228, with a gauge length of 7 mm, a width of 4 mm, and a thickness of 3 mm. Some specimens underwent a T6 heat treatment, which consisted of a solution treatment at 500°C for 2 hours, followed by water quenching and artificial aging at 200°C for 10 hours.
[0045] Tensile tests were conducted at room temperature and at 200°C on a universal tensile testing machine. At high temperature, the samples were heated in a test furnace and held there for 30 minutes to ensure uniform temperature. Tensile tests were performed using displacement control mode, with a loading rate set at 1 mm / min and a maximum load limit of 25 kN. An extensometer with an accuracy of ±1 με was used to record stress-strain data. The temperature ramp was omitted for room temperature stretching, which was otherwise similar. Yield strength, tensile strength, and elongation at break were measured for each sample group.
[0046] High-entropy alloy particle-reinforced 2xxx aluminum-based composites prepared via the aforementioned process demonstrated significant performance improvements compared to their unreinforced counterparts in tensile testing. The enhanced interfacial bonding achieved through mechanical-ultrasonic composite dispersion, along with optimal casting temperature control, fosters a multi-scale strengthening mechanism dominated by Orowan wrapping, interfacial pinning, and dislocation entanglement, resulting in high strength and ductility at both room temperature and elevated temperatures of 200°C.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a high entropy alloy particle reinforced 2xxx series aluminum-based composite material, characterized in that: The following steps are involved: The 2xxx series aluminum alloy is heated and melted, and stirred after cooling. High entropy alloy particles are added and an inert gas is introduced. Ultrasonic treatment is performed under continuous stirring, and a high entropy alloy particle-reinforced 2xxx series aluminum-based composite material is obtained after casting.
2. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: Calculated by weight percentage, the composition of the 2xxx series aluminum alloy material includes: Cu 3-6.8%, Mg 0.2-1.5%, Mn 0.2-1.5%, Si ≤0.5%, Fe ≤0.5%, Zn ≤0.25%, Cr ≤0.10%, Ti ≤0.15%, other impurities ≤0.15, and Al balance.
3. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: The high entropy alloy particles are FeCoCrNiAl x Ti y , where 0 <x≤1,0<y≤1。 4. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: The heating melting temperature is 750° C. and the holding time is 2 h.
5. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: The temperature is lowered to 580-720°C.
6. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: The inert gas is argon.
7. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: The stirring temperature is 680-720° C., the stirring speed is 400-600 rpm, and the stirring time is 5-15 min.
8. The method for preparing a high-entropy particle-reinforced 2xxx aluminum alloy material according to claim 1, wherein: The ultrasonic frequency is 15-25 kHz, the ultrasonic power is 800-1500 W, and the ultrasonic time is 5 minutes.
9. A high entropy alloy particle reinforced 2xxx series aluminum-based composite material, characterized in that: A high-entropy alloy particle-reinforced 2xxx series aluminum-based composite material prepared by the method according to any one of claims 1 to 8.